Determinants of the Utilization of Diversified Types of Professionals for Mental Health Reasons in a Montreal (Canadian) Catchment Area - Fleury, Marie-Josée (Glob J Health Sci, 2012)
The study was designed to identify factors associated with the diversity of professionals consulted by 212 individuals affected by at least one mental disorder in the past 12 months in a Montreal catchment area. For inclusion in the study, participants had to be aged 15 to 65 and reside in the study zone. A comprehensive set of variables were analyzed in accordance with the Andersen’s behavioural model of health service use. General practitioners, psychiatrists, and psychologists were the main professionals consulted in this study. Having post-secondary education, more than a single mental disorder, excellent relationships with neighbours, and (marginally) being a lifelong victim of violence were associated with higher numbers of professionals consulted. As this study highlights the large number of diversified professionals consulted for reason of mental disorders, shared care initiatives may prove beneficial. Greater effort could also be made in increasing services toward those deemed more vulnerable.